Bulk trash to nano treasure: Synthesis of two-dimensional brucite nanosheet from high-magnesium nickel slag. (20th January 2022) - Qian, Binbin; Liu, Huiling; Ma, Bing; Wang, Qianqian; Lu, Jun; Hu, Yueyang; Tang, Yuneng; Liu, Cheng; Dai, Baiqian
Abstract: Fabrication of high-value products from nickel slag, an otherwise solid waste not only enables the sustainable reclamation from hazardous waste but also promotes the nanomaterial multiplex synthesis through a wider range of feedstocks. However, researches on the preparation of two-dimensional nanomaterials from nickel slag are rarely reported. Herein, the synthesis of two-dimensional magnesium hydroxide (2D Mg(OH)2 ) nanosheet from a local high-magnesium nickel slag (HMNS) waste is demonstrated, and its subsequent thermal and optical properties were investigated. The (001)-facet-dominance Mg(OH)2 nanosheet was initially synthesized by leaching, precipitation and hydrothermal treatment with ethanol meditation. Through detailed characterizations and density functional theory (DFT) calculations, the role of ethanol was found to result in the lowest surface energy for the (001) facet of Mg(OH)2 while restricting the crystal growth on [001]. A final nanosheet structure with an averaged aspect ratio of 14.5 was thus synthesized, as opposed to only 1.6 in the absence of ethanol. The resultant 2D Mg(OH)2 bears weaker thermal stability and a larger band gap compared with the reference nanoparticles synthesized without ethanol addition. This research contributes a representative example of converting HMNS or any Mg-bearing solid wastes into valuable materials and may open a new avenue to synthesizing 2D materials from low-cost feedstocks. Graphical abstract: Image 1 Highlights: Two-dimensional Mg(OH)2 nanosheets were synthesized from the high-magnesium nickel slag. Through DFT calculation, the role of ethanol on the directional growth of Mg(OH)2 has been advanced on the atomic level. New understandings on the thermal stability and optical property for the facet-dependent Mg(OH)2 have been offered.